Insights into Intrinsic Atopic Dermatitis: immunogenicity, Dysbiosis, and Imaging (Reflectance Confocal Microscopy, Optical Coherence Tomography) - Gavrilita E; Silion SI; Bitca ML; Tatu AL (Dove Medical Press, 2024)
Elena Gavrilita,1,2 Simona Ioana Silion,1,2 Miruna Lorelei Bitca,1 Alin Laurentiu Tatu1- 3 1Dermatology Department, "Sf. Cuvioasa Parascheva" Clinical Hospital of Infectious Diseases, Galați, Romania; 2Multidisciplinary Integrated Center of Dermatological Interface Research MIC-DIR, "Dunărea de Jos" University, Galați, Romania; 3Clinical Medical Department, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, RomaniaCorrespondence: Elena Gavrilita, Tel +40746680485, Email dr.elenagavrilita@gmail.comAbstract: Atopic dermatitis (AD) is a frequent inflammatory condition that usually begins during early childhood, but it increasingly starts to debut, even in the elderly. Based on immunoglobulin E (IgE) levels and clinical features, two subsets of this disease have been recognized: intrinsic and extrinsic. When speaking about AD, most specialists think about filaggrin (FLG) mutations resulting in epidermal barrier defects, which is the case in most atopic patients, but some have a normal barrier, as seen by imaging, and still have specific clinical lesions along with metal allergies. Specific molecules (IL-10, IFN-γ, and HBD-3) have been shown to greatly impact the interactions between internal and external factors in this peculiar form of AD. A less-known protein, suprabasin, has been highlighted as a promising explanation for nickel anomalies in intrinsic AD.Keywords: atopy, OCT, RCM, HBD-3, IFN-γ, suprabasin